Utilization of Sustainable Materials to Enhance Geotechnical Characteristics of Soils - Subba Rao, G.V, Rama (International Journal of Engineering and Technology, 2018)
Geotechnical engineering can noticeably affect the sustainability of infrastructure development because of its beginning place in the construction practice. Utilization of waste materials for enhancing properties of the soil is a wise choice and is also one step towards accomplishing sustainable development. Application of by-products (viz., flay ash and rice husk ash) which could be defined as â€œsustainable materialsâ€, find special place in the modern-day soil stabilization and modification exercise. The preset paper aims at enhancing properties of expansive soil with inclusion of industrial by-products namely Rice Husk ash and Fly Ash. Further the present paper focuses on improving geotechnical characteristics of fine sand upon reinforcing with ground shredded rubber tire. Fine sand has a low angle of internal friction and which in turn has low shear strength. Reuse of waste materials is one area of research which attempts to makes geotechnical engineering practice sustainable.Â Â